Aplikasi Penggunaan Teknologi E-Banking Dalam Upaya Peningkatan Pelayanan Nasabah (Studi Kasus PT. Bank Muamalat KCP Stabat) - Latifah Rahman; Muhammad Saleh; Diyan Yusri (Al-Sharf: Jurnal Ekonomi Islam, 2022)
This study focuses on the discussion of the E-Banking aplication offered, the perceived barriers, and the improvement in customer service perceived by the E-Banking facilities offered by PT. Bank Muamalat Stabat Sub-Branch Office.  The research method used in this research is a descriptive qualitative research method with an empirical approach. People who are used as informants in this study are employees and customers who use the E-Banking product of PT. Bank Muamalat Stabat Sub-Branch Office. In this study, researchers used a collection technique, namely by means of observation, interviews, and documentation. Data analysis in this study consisted of data editing, data classification, data verification, data analysis, and drawing conclusions. The results of the study explain that the application of the use of E-Banking technology offered by PT. Bank Muamalat Sub-Branch Office Stabat that is Automatic Teller Machine, Sala Muamalat, Muamalat Internet Banking, Muamalat Mobile Banking, Virtual Account Muamalat, Muamalat Cash Management System, and Muamalat Outlets (Payment Point Online Bank). Barriers to the use of E-Banking technology at PT. Bank Muamalat Stabat Sub-Branch Office, namely unsupported network, lack of customer capability regarding the use of technology, and technical problems using E-Banking. There was an increase in the service perceived by customers with the E-Banking facilities offered by PT. Bank Muamalat Stabat Sub-Branch Office. The existence of E-Banking facilities improves the service that customers feel when transacting, starting from increasing convenience, speed, security, and trust.